2011
DOI: 10.1038/jp.2010.199
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal complications associated with ibuprofen therapy for patent ductus arteriosus

Abstract: Objective: To review intestinal complications associated with ibuprofen treatment of patent ductus arteriosus (PDA).Study Design: Data from preterm infants treated with ibuprofen were retrospectively reviewed. w 2 test and Fischer's exact test were used for univariate analyses. Multivariate analyses with logistic regression modeling were used to identify risk factors.Result: One hundred and two infants were treated with ibuprofen for PDA. Nine (9/102, 8.8%) infants developed spontaneous intestinal perforation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 36 publications
(49 reference statements)
0
9
0
1
Order By: Relevance
“…In this study, NEC occurred in 8.8% of the intravenous group and in 5.6% of the oral group. In a retrospective review of 102 preterm infants who were treated by intravenous ibuprofen, Rao et al 25 demonstrated that 8.8% of preterm infants developed SIP. The authors concluded that infants at lower gestational age were at risk of SIP when treated early with intravenous ibuprofen for symptomatic PDA.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, NEC occurred in 8.8% of the intravenous group and in 5.6% of the oral group. In a retrospective review of 102 preterm infants who were treated by intravenous ibuprofen, Rao et al 25 demonstrated that 8.8% of preterm infants developed SIP. The authors concluded that infants at lower gestational age were at risk of SIP when treated early with intravenous ibuprofen for symptomatic PDA.…”
Section: Discussionmentioning
confidence: 99%
“…First is that all the alternatives to close the PDA have negative effects. [24][25][26][27][28] A second one is that, with time, an important number of PDA's close spontaneously. [29][30][31] The third one is that this clinical condition has a wide range of severity.…”
Section: Introductionmentioning
confidence: 99%
“…INDO has stronger COX-1 inhibition which produces more severe gastrointestinal and renal side effects than COX-2 inhibition [1]. Though, studies evaluating the use of IBU for PDA therapy in ELGANs (Extremely Low Gestational Age Neonates) reported an increased risk of oliguria and spontaneous intestinal perforation and speculated difference in drug clearance and regional prostaglandin concentration in this population [23][24][25]. IBU has also been linked to pulmonary hypertension [25] and increased risk of chronic lung disease [26].…”
Section: Discussionmentioning
confidence: 99%